PENGARUH BRAND TRUST DAN ELEKTRONIK WORD OF MOUTH TERHADAP KEPUTUSAN PEMBELIAN DUO SISTER HIJAB - Ingrit Amanda; Marliza Ade Fitri (Yayasan Insani Mandiri Santani, 2022)
This study aims 1) To analyze the effect of Brand Trust on purchasing decisions at Duo sister hijab. 2) To analyze the influence of Electronic Word of Mouth on purchasing decisions in Duo sister hijab. 3) To analyze the influence of Brand Trust and Electronic Word of Mouth on purchasing decisions at Duo sister hijab. This type of research is a quantitative and quantitative approach. The method used in this research is descriptive method. The population in this study were all consumers of Duo Sister Hijab. Based on the results of research on the relationship between electronic word of mouth and brand trust with purchasing decisions on Duo sister hijab, the following conclusions can be drawn: 1) There is a positive and significant influence of brand trust (X1) on purchasing decisions (Y) Duo sister hijab Bengkulu. 2) There is a positive influence of electronic word of mouth (X2) on purchasing decisions (Y Duo sister hijab Bengkulu Regency. 3) Brand trust and electronic word of mouth together affect the performance of Duo sister hijab Bengkulu Regency. Keywords: Brand Trust, Electronic Word Of Mouth and Purchase Decision